Obtaining porous silicon suitable for sensor technology using MacEtch nonelectrolytic etching - Iatsunskyi, I. R. (Technology and design in electronic equipment, 2013)
The author suggests using the etching method MacEtch (metal-assisted chemical etching) for production of micro- and nanostructures of porous silicon. The paper presents research results on the morphology structures obtained at different parameters of deposition and etching processes. The research has shown that, depending on the parameters of deposition of silver particles and silicon wafers etching, the obtained surface morphology may be different. There may be both individual crater-like pores and developed porous or macroporous surface. These results indicate that the MacEtch etching is a promising method for obtaining microporous silicon nanostructures suitable for effective use in gas sensors and biological object sensors.